Front Cover: Synthesis of Actinide Fluoride Complexes Using Trimethyltin Fluoride as a Mild and Selective Fluorinating Reagent (Eur. J. Inorg. Chem. 11/2018). Issue 11 (12th February 2018) - Kagan, Benjamin D.; Lichtscheidl, Alejandro G.; Erickson, Karla A.; Monreal, Marisa J.; Scott, Brian L.; Nelson, Andrew T.; Kiplinger, Jaqueline L.
Abstract : The Front Cover shows the versatility of trimethyltin fluoride (Me3 SnF) as a reagent for the conversion of actinide halides to actinide fluorides. Me3 SnF is used with a suite of organometallic actinide chloride, bromide, and iodide complexes towards the synthesis of actinide fluorides. This route is not limited by metal (thorium vs. uranium), oxidation state [uranium(IV) vs. uranium(V)], or ligand platform (metallocene vs. non‐metallocene). This methodology opens a new gateway for accessing terminal actinide fluorides and studying their chemistry. More information can be found in theFull Paper by J. L. Kiplinger et al. For more on the story behind the cover research, see theCover Profile .